Negative plate, preparation method thereof and battery
By designing a multi-layer structure in the negative electrode sheet of the lithium-ion battery, using the characteristics of carbon-based materials and tin-based materials, combined with the protective layer of modified lithium titanate, the problem of poor volume expansion and cycle stability of the SnO2 negative electrode in the lithium-ion battery is solved, and the service life and safety of the battery are improved.
Patent Information
- Application Number
- CN202510329369.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-06-27
AI Technical Summary
The SnO2 negative electrode expands in a lithium-ion battery after being embedded in lithium-ion batteries, with large irreversible capacity for the first time, and poor circulation stability.
The negative electrode sheet design is adopted with a multi-layer structure, wherein the first negative electrode coating comprises a carbon-based material, the second negative electrode coating comprises a tin-based material, and the third negative electrode coating comprises a modified lithium titanate. With this structure, the low expansion rate of the carbon-based material and the protective layer of the modified lithium titanate are used to reduce the peeling phenomenon between the active material and the current collector.
It improves the service life and safety of lithium-ion batteries, avoids side reactions caused by contact between tin-based materials and current collectors and electrolytes, and enhances the battery's circulation capacity retention rate and long-term stability.
Smart Images

Figure BDA0005320005960000161 
Figure BDA0005320005960000171
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular, to a negative electrode sheet, a preparation method thereof, and a battery. Background Art
[0002] In order to meet the growing energy demands of modern society, the development of lithium-ion batteries with high energy density and long cycle life has become a key goal in battery research. The key to determining the energy density of lithium batteries is the selection of the positive and negative electrode materials. Currently, high-energy-density battery cells mainly use high-nickel ternary and graphite as the positive and negative electrode materials. In the case of an increasing demand for high energy density, the room for improving the energy density of the current high-nickel ternary positive electrode is limited, and the capacity of the negative electrode graphite is approaching the theoretical limit.
[0003] Tin (Sn)-based oxides have higher lithium storage capacity, thermal stability, and more diverse adjustable micro-nano structures. The theoretical mass specific capacity of tin dioxide (SnO2) is 1494 mAh / g (graphite: 372 mAh / g), and the volume specific capacity is even as high as 10220 mAh / cm 3 , which is higher than that of Si negative electrodes (9744 mAh / cm 3 ) and Li negative electrodes (2277 mAh / cm 3 ). If the SnO2 negative electrode can be practically applied, it will greatly improve the specific capacity and energy density of the lithium-ion battery system. However, the SnO2 negative electrode has problems such as large volume expansion after lithium ions are inserted, large first irreversible capacity, and poor cycle stability.
[0004] Therefore, it is necessary to take effective measures to solve the problems of large volume expansion, large first irreversible capacity, and poor cycle stability of the SnO2 negative electrode after lithium ions are inserted, so that the SnO2 negative electrode can be applied to lithium-ion batteries. Summary of the Invention
[0005] In view of this, the present invention aims to solve at least one of the technical problems in the related art to some extent. For this reason, the present invention provides a negative electrode sheet, a preparation method thereof, and a battery, which can solve the problems of large volume expansion, large first irreversible capacity, and poor cycle stability of the SnO2 negative electrode after lithium ions are inserted.
[0006] To solve the above technical problems, the present application is implemented as follows:
[0007] According to one aspect of the present application, an embodiment of the present application provides a negative electrode sheet, which includes:
[0008] A current collector;
[0009] A first negative electrode coating disposed on at least one surface of the current collector in the thickness direction, and the first negative electrode coating includes a carbon-based material;
[0010] A second negative electrode coating, disposed on a surface of the first negative electrode coating away from the current collector, the second negative electrode coating including a tin-based material; and
[0011] A third negative electrode coating, disposed on a surface of the second negative electrode coating away from the first negative electrode coating, the third negative electrode coating including modified lithium titanate.
[0012] In some embodiments thereof, the carbon-based material includes hard carbon and graphite.
[0013] In some embodiments thereof, a mass ratio of the hard carbon to the graphite is (5 to 15):(85 to 95).
[0014] In some embodiments thereof, the graphite includes at least one of graphitized needle coke, graphitized pitch tar, and graphitized petroleum coke; preferably, the graphite is selected from graphitized petroleum coke.
[0015] In some embodiments thereof, the first negative electrode coating further includes a first conductive agent and a first binder.
[0016] In some embodiments thereof, a mass ratio of the carbon-based material, the first conductive agent, and the first binder is (90 to 110):(0.3 to 1):(2 to 3).
[0017] In some embodiments thereof, the first conductive agent includes at least one of conductive carbon black, conductive carbon fiber, graphene, or conductive carbon nanotube.
[0018] In some embodiments thereof, the first binder includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium alginate, or polyacrylic acid.
[0019] In some embodiments thereof, a thickness of the first negative electrode coating is 5 μm to 50 μm.
[0020] In some embodiments thereof, the tin-based material includes at least one of tin, tin oxide compound, and tin alloy.
[0021] In some embodiments thereof, the tin-based material includes a tin dioxide-based composite iron trioxide oxide.
[0022] In some embodiments thereof, the second negative electrode coating further includes a second conductive agent and a second binder.
[0023] In some embodiments thereof, a mass ratio of the tin-based material, the second conductive agent, and the second binder is (90 to 96):(0.5 to 1):(2 to 3.5).
[0024] In some of these embodiments, the second conductive agent includes at least one of conductive carbon black, conductive carbon fiber, graphene, or conductive carbon nanotubes.
[0025] In some of these embodiments, the second binder includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium alginate, or polyacrylic acid.
[0026] In some of these embodiments, the thickness of the second negative electrode coating is 40 μm to 100 μm.
[0027] In some of these embodiments, the modified lithium titanate includes a modifier and lithium titanate, and the modifier is coated on at least a part of the surface of the lithium titanate.
[0028] In some of these embodiments, the mass ratio of lithium titanate to the modifier in the modified lithium titanate is (85 to 95):(5 to 15).
[0029] In some of these embodiments, the modifier includes lithium phosphate, lithium dihydrogen phosphate, lithium sulfate, or lithium sulfite.
[0030] In some of these embodiments, the third negative electrode coating further includes a third conductive agent and a third binder.
[0031] In some of these embodiments, the mass ratio of the modified lithium titanate, the third conductive agent, and the third binder is (90 to 95):(1 to 2):(1.5 to 3).
[0032] In some of these embodiments, the third conductive agent includes at least one of conductive carbon black, conductive carbon fiber, graphene, or conductive carbon nanotubes.
[0033] In some of these embodiments, the third binder includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium alginate, or polyacrylic acid.
[0034] In some of these embodiments, the thickness of the third negative electrode coating is 5 μm to 20 μm.
[0035] In some of these embodiments, the current collector includes at least one of copper foil, nickel foam, nickel mesh, or composite copper foil.
[0036] According to another aspect of the present application, embodiments of the present application provide a method for preparing a negative electrode sheet, including the following steps:
[0037] Coat a first negative electrode slurry on at least one surface of the current collector to obtain a first negative electrode coating;
[0038] Coat a second negative electrode slurry on the surface of the first negative electrode coating to obtain a second negative electrode coating;
[0039] Coat a third negative electrode slurry on the surface of the second negative electrode coating to obtain a third negative electrode coating;
[0040] Roll and dry the current collector coated with the first negative electrode coating, the second negative electrode coating, and the third negative electrode coating;
[0041] Among them, the first negative electrode coating includes a carbon-based material;
[0042] The second negative electrode coating includes a tin-based material;
[0043] The third negative electrode coating includes modified lithium titanate.
[0044] In some embodiments, the preparation of the first negative electrode slurry includes: mixing hard carbon, graphite, a first conductive agent, and a first binder uniformly in a solvent to obtain the first negative electrode slurry.
[0045] In some embodiments, the preparation of the second negative electrode slurry includes: mixing a tin-based material, a second conductive agent, and a second binder uniformly in a solvent to obtain the second negative electrode slurry.
[0046] In some embodiments, the preparation of the third negative electrode slurry includes: mixing modified lithium titanate, a third conductive agent, and a third binder uniformly in a solvent to obtain the third negative electrode slurry.
[0047] In some embodiments, the compaction density of the rolling is 1.45 - 1.65 g / cm 3 .
[0048] In some embodiments, the solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, N-methylpyrrolidone, water, or ethylene carbonate.
[0049] In some embodiments, coat the first negative electrode slurry on the surface of the current collector, and after drying, form a first negative electrode coating on the surface of the current collector; coat the second negative electrode slurry on the first negative electrode coating, and after drying, form a second negative electrode coating on the surface of the first negative electrode coating; coat the third negative electrode slurry on the second negative electrode coating and dry; after rolling and drying the current collector coated with the first negative electrode coating, the second negative electrode coating, and the third negative electrode coating, obtain a negative electrode sheet.
[0050] In some embodiments, the tin-based material includes a tin dioxide-based composite iron(III) oxide, and the preparation method of the tin dioxide-based composite iron(III) oxide includes:
[0051] Mix a stannous salt solution with a ferrocyanide salt solution, and form a tin-based cyanogel precursor through a sol-gel process. After drying and washing, a tin dioxide-based composite iron oxide is obtained; the molar ratio of the stannous salt to the ferrocyanide salt is (6-8):(2-4).
[0052] In some of these embodiments, the concentration of the stannous salt solution is 2 mol / L to 4 mol / L.
[0053] In some of these embodiments, the drying temperature is 500°C to 700°C, and the time is 5 h to 7 h.
[0054] In some of these embodiments, the preparation method of the modified lithium titanate includes:
[0055] Mix a modifier, an auxiliary agent, and lithium titanate, then ball-mill them, and then heat them in an inert atmosphere to obtain modified lithium titanate.
[0056] In some of these embodiments, the molar ratio of the modifier, the auxiliary agent, and lithium titanate is (0.8-1.2):(0.8-1.2):(8-12).
[0057] In some of these embodiments, the rotation speed of the ball-milling is 200 r / min to 400 r / min, and the time is 0.5 h to 2 h.
[0058] In some of these embodiments, the heating temperature is 700°C to 900°C, and the time is 4 h to 6 h.
[0059] According to another aspect of the present application, an embodiment of the present application provides a battery, including a negative electrode sheet, and the negative electrode sheet includes the aforementioned negative electrode sheet, or includes the negative electrode sheet prepared by the aforementioned preparation method.
[0060] Implementing the technical solution of the present invention has at least the following beneficial effects:
[0061] In the embodiments of the present application, the provided negative electrode sheet is provided with a carbon-based material in the first negative electrode coating, a tin-based material in the second negative electrode coating, and a modified lithium titanate in the third negative electrode coating. Thus, by utilizing the characteristic of the carbon-based material having a low expansion rate, the occurrence of the peeling phenomenon between the active material and the current collector due to volume change during the preparation process of the negative electrode sheet or during the charge and discharge process of the battery is reduced; moreover, there is a better adhesion between the carbon-based material and the current collector. Therefore, the service life and safety of the battery can be improved. Further, setting the tin-based material in the second negative electrode coating can prevent the tin-based material from directly contacting the current collector and the electrolyte. First, this setting method can avoid the occurrence of peeling from the current collector due to the high volume change rate of the tin-based material; second, it can avoid side reactions when the tin-based material contacts the electrolyte, thereby reducing the consumption of active lithium and the capacity attenuation of the battery, and improving the cycle capacity retention rate and long-term stability of the battery. Furthermore, the third negative electrode coating contains modified lithium titanate, and the modified lithium titanate contains a modifier (such as lithium phosphate), where the SEI in the modifier can accelerate the interfacial transport of lithium ions because the desolvation process is more likely to occur at the electrode-electrolyte interface, hindering the contact between the solvent molecules and the electrode, suppressing the solvent decomposition, resulting in the formation of a thinner SEI, and reducing the ion transport resistance within the SEI.
[0062] Additional aspects and advantages of the present application will be given in part in the following description, become apparent in part from the following description, or be understood through the practice of the present invention. Detailed Embodiments
[0063] The following further elaborates the present application in combination with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and not to limit the scope of the present application.
[0064] In the ranges disclosed herein, the endpoints and any values are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values and individual point values of each range, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.
[0065] If there is no special indication, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0066] If there is no special indication, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0067] Unless otherwise specified, all steps of this application can be carried out sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) carried out sequentially, or may also include steps (b) and (a) carried out sequentially. For example, it is mentioned that the method may further include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may also include steps (a), (c) and (b), or may also include steps (c), (a) and (b), etc.
[0068] Unless otherwise specified, "including" and "comprising" mentioned in this application mean open-ended, and can also be closed-ended. For example, the "including" and "comprising" may mean that other components not listed can also be included or comprised, or may only include or comprise the listed components.
[0069] In the prior art, the presence of tin-based materials can significantly improve the energy density of the battery, but the volume expansion during the lithium insertion process of the tin-based anode material itself will bring problems such as fast cycle decay, low initial efficiency, and electrode expansion.
[0070] In view of this, an embodiment of this application provides an anode sheet, which includes:
[0071] A current collector;
[0072] A first anode coating, disposed on at least one surface of the current collector along the thickness direction, and the first anode coating includes a carbon-based material;
[0073] A second anode coating, disposed on the surface of the first anode coating away from the current collector, and the second anode coating includes a tin-based material; and
[0074] A third anode coating, disposed on the surface of the second anode coating away from the first anode coating, and the third anode coating includes modified lithium titanate.
[0075] The provided anode sheet has a multi-layer structure, which includes a current collector, a first anode coating, a second anode coating, and a third anode coating that are sequentially stacked, that is, a first anode coating is disposed on at least one surface of the current collector, a second anode coating is disposed on the surface of the first anode coating, and a third anode coating is disposed on the surface of the second anode coating. Among them, the first anode coating can be used as a carbon-based material layer, the second anode material layer can be used as a tin-based material layer, and the third anode coating can be used as an interface improvement layer. It can be understood that starting from the current collector from bottom to top, a carbon-based material layer, a tin-based material layer, and a modified lithium titanate layer are disposed.
[0076] The above "the first negative electrode coating is disposed on at least one surface of the current collector in the thickness direction" means that the first negative electrode coating can be disposed on one surface of the current collector in its own thickness direction, or can be disposed on two surfaces of the current collector in its own thickness direction. The "surface" here can be the entire area of the current collector or a partial area of the current collector. For example, in this embodiment, the surface can be the entire area of the current collector. The present application has no particular limitation on this, as long as the purpose of the present application can be achieved.
[0077] As an example, the current collector has two surfaces opposite to each other in its own thickness direction, and the first negative electrode coating is disposed on the two opposite surfaces of the current collector. Further, a second negative electrode coating is formed on the surfaces of the first negative electrode coatings on both sides. Still further, a third negative electrode coating is formed on the surfaces of the second negative electrode coatings on both sides. It can be understood that in other embodiments, the first negative electrode coating can also be stacked on any one of the two surfaces of the current collector.
[0078] In the present application, in the negative electrode sheet, the material of the current collector is not particularly limited.
[0079] In the present application, in the negative electrode sheet, the first negative electrode coating contains a carbon-based material. Compared with a tin-based material, the carbon-based material has a lower expansion rate, reducing the occurrence of peeling between the active material and the current collector due to volume change during the preparation process of the negative electrode sheet or during the charge and discharge process of the battery; and, the carbon-based material has a better adhesion to the current collector. Thus, the service life and safety of the battery can be improved.
[0080] In the present application, in the negative electrode sheet, the material of the second negative electrode coating contains a tin-based material. By disposing the tin-based material in the second negative electrode coating, it is possible to prevent the tin-based material from directly contacting the current collector and the electrolyte. First, this setting method can prevent the occurrence of peeling from the current collector due to the high volume change rate of the tin-based material; second, it can prevent side reactions from occurring after the tin-based material contacts the electrolyte, thereby reducing the consumption of active lithium and capacity attenuation of the battery, and improving the cycle capacity retention rate and long-term stability of the battery.
[0081] In this application, in the negative electrode sheet, the third negative electrode coating contains modified lithium titanate. The modified lithium titanate contains lithium phosphate, and the SEI in the lithium phosphate can accelerate the interfacial transport of lithium ions. The desolvation process is more likely to occur at the electrode-electrolyte interface, which hinders the contact between solvent molecules and the electrode, inhibits solvent decomposition, resulting in the formation of a thinner SEI, and reduces the ion transport resistance within the SEI. Coating a layer of modified lithium titanate on the tin-based negative electrode layer can form a good protective layer, avoiding side reactions caused by the contact between the expanded tin-based negative electrode and the electrolyte, and improving the first efficiency, capacity, cycle stability and safety of the battery. Lithium titanate has poor conductivity. In the present invention, modified lithium titanate is selected, which can increase the diffusion and migration rate of lithium ions in the modified lithium titanate layer and improve the charging ability of the battery cell.
[0082] Thus, in the negative electrode sheet of this application, a carbon-based material is provided in the first negative electrode coating, a tin-based material is provided in the second negative electrode coating, and modified lithium titanate is provided in the third negative electrode coating. Thereby, by utilizing the characteristic that the carbon-based material has a lower expansion rate, the occurrence of the peeling phenomenon between the active material and the current collector due to volume change during the preparation process of the negative electrode sheet or during the charge and discharge process of the battery is reduced; moreover, there is a better adhesion between the carbon-based material and the current collector. Therefore, the service life and safety of the battery can be improved. Further, setting the tin-based material in the second negative electrode coating can avoid the direct contact between the tin-based material and the current collector and the electrolyte. First, this setting method can avoid the occurrence of peeling from the current collector due to the high volume change rate of the tin-based material; second, it can avoid side reactions after the tin-based material contacts the electrolyte, thereby reducing the consumption of active lithium and the capacity attenuation of the battery, and improving the cycle capacity retention rate and long-term stability of the battery. Furthermore, the third negative electrode coating contains modified lithium titanate, and the modified lithium titanate contains a modifier (such as lithium phosphate), and the SEI in the modifier can accelerate the interfacial transport of lithium ions because the desolvation process is more likely to occur at the electrode-electrolyte interface, which hinders the contact between solvent molecules and the electrode, inhibits solvent decomposition, resulting in the formation of a thinner SEI, and reduces the ion transport resistance within the SEI.
[0083] In some embodiments, the carbon-based material includes hard carbon and graphite.
[0084] In some embodiments, the mass ratio of hard carbon to graphite is (5-15):(85-95). As an example, the mass ratio of hard carbon to soft carbon can be 5:85, 10:90, 15:95. Of course, it can also be a certain ratio within the above range, and no specific limitation is made here. Mixing a small amount of hard carbon in graphite is because the hard carbon material has a small lithium insertion strain and a small volume expansion during charge and discharge. After mixing hard carbon, the expansion of graphite can be reduced, thereby reducing the overall expansion of the negative electrode. However, if the mass ratio of hard carbon to graphite is higher than 15:95, the proportion of hard carbon will be relatively high and the proportion of graphite will be low. The conductivity of hard carbon is poorer than that of graphite and the compaction density is low, which will affect the overall kinetic performance and energy density of the electrode sheet; if the mass ratio of hard carbon to graphite is lower than 5:85, the proportion of hard carbon will be relatively small and the proportion of graphite will be large, and the rebound of the electrode sheet of the carbon-based material layer will be relatively large, and the inhibitory effect on the overall expansion of the electrode sheet will be weak.
[0085] In some embodiments, the graphite includes, but is not limited to, at least one of graphitized needle coke, graphitized pitch tar, and graphitized petroleum coke; preferably, the graphite is selected from graphitized petroleum coke. This kind of graphite has a small rebound and can reduce the rebound of the overall negative electrode sheet to a greater extent.
[0086] In some embodiments, the first negative electrode coating further includes a first conductive agent and a first binder.
[0087] In some embodiments, the mass ratio of the carbon-based material, the first conductive agent, and the first binder is (90-110):(0.3-1):(2-3). As an example, the mass ratio of the carbon-based material, the first conductive agent, and the first binder can be 90:0.3:1, 100:0.5:2.5, 110:1:3. Of course, it can also be a certain ratio within the above range, and no specific limitation is made here.
[0088] In some embodiments, the first conductive agent includes, but is not limited to, at least one of conductive carbon black, conductive carbon fiber, graphene, or conductive carbon nanotube. As an example, the first conductive agent can be conductive carbon black or conductive carbon fiber.
[0089] In some embodiments, the first binder includes, but is not limited to, at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium alginate, or polyacrylic acid. As an example, the first binder can be polyvinylidene fluoride or sodium carboxymethyl cellulose.
[0090] In some embodiments, the thickness of the first negative electrode coating is 5 μm to 50 μm. As an example, the thickness of the first negative electrode coating can be 5 μm, 15 μm, 25 μm, 35 μm, 45 μm, 50 μm, and of course it can also be a point value within the above range, which is not specifically limited here. The appropriate thickness of the first negative electrode coating can, on the one hand, effectively prevent the contact between the tin-based material and the current collector, improve the adhesion of the membrane, and avoid the membrane peeling caused by the expansion of the tin-based material during long-term circulation, thereby improving the cycle stability and safety of the battery. On the other hand, it can enable the capacity of the negative electrode sheet to be effectively utilized to the maximum extent. The tin-based material has a high lithium embedding capacity, while graphite and hard carbon have relatively low capacity. The appropriate thickness of the graphite and hard carbon composite layer can solve the poor adhesion between the tin-based negative electrode and the current collector, inhibit the large volume expansion of the tin-based negative electrode during the cycle process, and modify the de-filming phenomenon of the active material. On the other hand, it will not cause the overall capacity of the negative electrode material to lose too much, and the negative electrode will have as much capacity as possible.
[0091] In some embodiments, the tin-based material includes, but is not limited to, at least one of simple tin, tin oxide, and tin alloy. As an example, the tin-based material can be simple tin or tin oxide.
[0092] In some embodiments, the tin-based material includes tin dioxide-based composite iron oxide, wherein the tin dioxide-based composite iron oxide has a three-dimensional nanostructure, which can provide a larger lithium storage space and effectively improve the capacity of the battery.
[0093] In some embodiments, the second negative electrode coating further includes a second conductive agent and a second binder.
[0094] In some embodiments, the mass ratio of the tin-based material, the second conductive agent, and the second binder is (90-96): (0.5-1): (2-3.5). As an example, the mass ratio of the tin-based material, the second conductive agent, and the second binder can be 90:0.5:2, 93:0.8:3, 96:1:3.5, and of course it can be a ratio within the above range, which is not specifically limited here.
[0095] In some embodiments, the second conductive agent includes, but is not limited to, at least one of conductive carbon black, conductive carbon fiber, graphene, or conductive carbon nanotubes. As an example, the second conductive agent may be conductive carbon black or conductive carbon fiber.
[0096] In some embodiments, the second binder includes, but is not limited to, at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium alginate, or polyacrylic acid. As an example, the second binder may be polyvinylidene fluoride, sodium carboxymethyl cellulose, or a mixture of polyvinylidene fluoride and sodium carboxymethyl cellulose.
[0097] In some embodiments, the thickness of the second negative electrode coating is 40 μm to 100 μm. As an example, the thickness of the second negative electrode coating can be 40 μm, 60 μm, 80 μm, 100 μm. Of course, it can also be a point value within the above range, and no specific limitation is made here.
[0098] In some embodiments, the modified lithium titanate includes a modifier and lithium titanate, and the modifier coats at least a part of the surface of the lithium titanate. The lithium titanate material is a zero-variance material, which is extremely stable during charge and discharge and will not form an SEI film to consume too much active lithium. Its lithium potential is relatively high at 1.5 V. Even in the later stage of charging, at low temperature or under high-rate charging conditions, it will not reach the potential at which lithium ions are reduced to metallic lithium, avoiding the formation of lithium dendrites during overcharging of the battery and having better safety. Coating a layer of lithium titanate layer on the upper layer of the tin-based composite layer can form a good protective layer to prevent the swollen tin-based negative electrode from contacting the electrolyte to occur side reactions, improving the first efficiency, capacity, cycle stability and safety of the battery. However, lithium titanate has the disadvantage of poor conductivity. In the present invention, the lithium titanate is modified (which can improve the conductivity of lithium titanate, and the modifier is equivalent to an SEI film and does not change the advantages inherent in lithium titanate itself), improving the diffusion and migration rate of lithium ions in the lithium titanate layer (the third negative electrode coating), and thus improving the fast charging ability of the battery.
[0099] In some embodiments, the mass ratio of lithium titanate to the modifier in the modified lithium titanate is (85 - 95):(5 - 15). As an example, the mass ratio of lithium titanate to the modifier can be 85:5, 90:10, 95:15. Of course, it can also be a ratio within the above range, and no specific limitation is made here.
[0100] In some embodiments, the modifier is beneficial to Li + to be desolvated from the solvation sheath. The fundamental reason is that the modifier provides electrons with lower energy and can more easily provide electrons to act as an adsorbed electron donor for solvated Li + , reducing the interaction between Li + and solvent molecules and accelerating the desolvation kinetics. Thereby increasing the diffusion and migration rate of Li + in the lithium titanate layer and improving the charging ability of the battery cell.
[0101] In some embodiments, the modifier includes, but is not limited to, lithium phosphate, lithium dihydrogen phosphate, lithium sulfate, and lithium sulfite. As an example, the modifier can be lithium phosphate, or it can be lithium sulfate, preferably lithium phosphate. The modifier lithium phosphate can coat at least part of the surface of lithium titanate. The presence of lithium phosphate facilitates the desolvation process of lithium ions. Since the energy for lithium phosphate to provide electrons is relatively low (5.2 eV), it can more easily provide electrons to act as an adsorbed electron donor for solvated lithium ions, reducing the interaction between lithium ions and solvent molecules, thereby accelerating the desolvation kinetics. As a result, the diffusion and migration rate of lithium ions in the lithium titanate layer is increased, and the charging capacity of the battery is improved.
[0102] In some embodiments, the third negative electrode coating further includes a third conductive agent and a third binder.
[0103] In some embodiments, the mass ratio of the modified lithium titanate, the third conductive agent, and the third binder is (90 - 95):(1 - 2):(1.5 - 3). As an example, the mass ratio of the modified lithium titanate, the third conductive agent, and the third binder can be 90:1:1.5, 93:1.5:2, 95:2:3. Of course, it can also be a certain ratio within the above range, and no specific limitation is made here.
[0104] In some embodiments, the third conductive agent includes, but is not limited to, at least one of conductive carbon black, conductive carbon fiber, graphene, or conductive carbon nanotubes. As an example, the third conductive agent can be conductive carbon black, or it can be conductive carbon fiber.
[0105] In some embodiments, the third binder includes, but is not limited to, at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium alginate, or polyacrylic acid. As an example, the third binder can be polyvinylidene fluoride, or it can be sodium carboxymethyl cellulose.
[0106] In some embodiments, the thickness of the third negative electrode coating is 5 μm - 20 μm. As an example, the thickness of the third negative electrode coating can be 5 μm, 10 μm, 15 μm, 20 μm. Of course, it can also be a certain point value within the above range, and no specific limitation is made here.
[0107] It can be understood that the mass ratios of the carbon-based material, the first conductive agent, and the first binder, the tin-based material, the second conductive agent, and the second binder, and the modified lithium titanate, the third conductive agent, and the third binder are related to the electrochemical performance of the corresponding battery and further affect the structural stability of the negative electrode sheet. By controlling the ratios of the substances in the first negative electrode coating, the second negative electrode coating, and the third negative electrode coating within the above ranges, the functions of each material are fully exerted, effectively improving the cycle performance, fast charging performance, and structural stability of the negative electrode sheet.
[0108] It can also be understood that the thickness of the coating affects the electrical performance of the battery (such as energy density, cycle performance, and rate performance), manufacturing cost, and safety performance. If the thicknesses of the first negative electrode coating, the second negative electrode coating, and the third negative electrode coating are too large, the electron transport distance increases, the electron resistance increases, the rate performance decreases, which has an adverse effect on the electrical performance of the battery, and further increases the difficulty of battery thermal management. However, if the thicknesses of the first negative electrode coating, the second negative electrode coating, and the third negative electrode coating are too low, the improvement of the structural stability of the negative electrode sheet is not obvious, which has an adverse effect on the safety and long-term cycle stability of the battery.
[0109] In some embodiments, the current collector includes at least one of copper foil, nickel foam, nickel mesh, or composite copper foil. As an example, the current collector can be copper foil or nickel foam.
[0110] Thus, based on the above, a negative electrode sheet is provided. By providing a carbon-based material in the first negative electrode coating, a tin-based material in the second negative electrode coating, and a modified lithium titanate in the third negative electrode coating. Thereby, taking advantage of the characteristic of the carbon-based material having a low expansion rate, the occurrence of the peeling phenomenon between the active material and the current collector due to volume change during the preparation process of the negative electrode sheet or during the charge and discharge process of the battery is reduced; moreover, there is a better adhesion between the carbon-based material and the current collector. Therefore, the service life and safety of the battery can be improved. By controlling the thickness of the first negative electrode coating, on the one hand, it can effectively prevent the contact between the tin-based material and the current collector, improve the adhesion of the film, and avoid the film peeling phenomenon caused by the expansion of the tin-based material during long-term cycling, improving the cycle stability and safety of the battery. On the other hand, it can enable the capacity of the negative electrode sheet to be effectively exerted to the greatest extent. The tin-based material has a high lithium intercalation capacity, while graphite and hard carbon have relatively low capacities. An appropriate thickness of the graphite and hard carbon composite layer can solve the problem of poor adhesion between the tin-based negative electrode and the current collector, inhibit the large volume expansion of the tin-based negative electrode during cycling, and the phenomenon of the modified active substance peeling off the film. On the other hand, it will not cause excessive capacity loss of the overall negative electrode material, and enables the negative electrode to have as large a capacity as possible.
[0111] Furthermore, setting the tin-based material in the second negative electrode coating can avoid the direct contact between the tin-based material and the current collector and the electrolyte. First of all, this setting method can avoid the occurrence of the peeling situation between the tin-based material and the current collector due to the high volume change rate of the tin-based material; secondly, it can avoid side reactions when the tin-based material contacts the electrolyte, thereby reducing the consumption of active lithium and capacity attenuation of the battery, and improving the cycle capacity retention rate and long-term stability of the battery.
[0112] Further, the third negative electrode coating contains modified lithium titanate. The modifier is coated on at least a part of the surface of lithium titanate to modify the lithium titanate. Since the lithium titanate material is a zero-variant material, it is extremely stable during charge and discharge, and no SEI film will be formed to consume too much active lithium. Its lithium potential is relatively high at 1.5V. Even in the later stage of charging, at low temperature or during high-rate charging, it will not reach the potential at which lithium ions are reduced to metallic lithium, avoiding the generation of lithium dendrites during overcharging of the battery and having better safety. Coating a layer of lithium titanate on the upper layer of the tin-based composite layer can form a good protective layer to prevent the swollen tin-based negative electrode from contacting the electrolyte and undergoing side reactions, improving the initial efficiency, capacity, cycle stability and safety of the battery. However, lithium titanate has the disadvantage of poor conductivity. In the present invention, the lithium titanate is modified. The modifier coated on the surface of lithium titanate can form an SEI film. At the same time, lithium ions are more likely to undergo a desolvation process at the electrode-electrolyte interface, hindering the contact between solvent molecules and the electrode, suppressing solvent decomposition, and thus forming a thinner SEI and reducing the ion transport resistance within the SEI. Therefore, the diffusion and migration speed of lithium ions in the lithium titanate layer (the third negative electrode coating) can be increased, and the rapid charging ability of the battery can be improved accordingly.
[0113] Based on the same inventive concept, an embodiment of the present application provides a method for preparing a negative electrode sheet, including the following steps:
[0114] Coating a first negative electrode slurry on at least one surface of a current collector to obtain a first negative electrode coating;
[0115] Coating a second negative electrode slurry on the surface of the first negative electrode coating to obtain a second negative electrode coating;
[0116] Coating a third negative electrode slurry on the surface of the second negative electrode coating to obtain a third negative electrode coating;
[0117] Rolling and drying the current collector coated with the first negative electrode coating, the second negative electrode coating, and the third negative electrode coating;
[0118] Wherein, the first negative electrode coating includes a carbon-based material;
[0119] The second negative electrode coating includes a tin-based material;
[0120] The third negative electrode coating includes modified lithium titanate.
[0121] It should be understood that all the features and advantages described above for the "negative electrode sheet" also apply to the "method for preparing a negative electrode sheet", and will not be repeated here one by one.
[0122] In some embodiments, the preparation of the first negative electrode slurry includes: uniformly mixing hard carbon, graphite, a first conductive agent, and a first binder in a solvent to obtain the first negative electrode slurry.
[0123] In some embodiments, the preparation of the second negative electrode paste includes: mixing a tin-based material, a second conductive agent, and a second binder uniformly in a solvent to obtain the second negative electrode paste.
[0124] In some embodiments, the preparation of the third negative electrode paste includes: mixing modified lithium titanate, a third conductive agent, and a third binder uniformly in a solvent to obtain the third negative electrode paste.
[0125] In some embodiments, the compaction density after roll pressing is 1.45 g / cm 3 ~1.65 g / cm 3 . As an example, the compaction density after roll pressing can be 1.45 g / cm 3 , 1.55 g / cm 3 , 1.65 g / cm 3 . Of course, it can also be a certain point value within the above range, and no specific limitation is made here.
[0126] In some embodiments, the solvent includes, but is not limited to, at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, N-methylpyrrolidone, water, or ethylene carbonate. As an example, the solvent can be dimethyl carbonate, can be diethyl carbonate, or can be water.
[0127] In some embodiments, the first negative electrode paste is coated on the surface of the current collector, and after drying, a first negative electrode coating is formed on the surface of the current collector; the second negative electrode paste is coated on the first negative electrode coating, and after drying, a second negative electrode coating is formed on the surface of the first negative electrode coating; the third negative electrode paste is coated on the second negative electrode coating and dried; after roll pressing and drying the current collector coated with the first negative electrode coating, the second negative electrode coating, and the third negative electrode coating, a negative electrode sheet is obtained.
[0128] In some embodiments, the tin-based material includes a tin dioxide-based composite iron(III) oxide, and the preparation method of the tin dioxide-based composite iron(III) oxide includes:
[0129] Mixing a tin salt solution and a ferricyanide solution, forming a tin-based cyanogel precursor through a sol-gel process, and after drying and washing, obtaining the tin dioxide-based composite iron(III) oxide.
[0130] In the present invention, the tin-based cyanogel system is used as a precursor, which has a three-dimensional nanoporous space network structure. Therefore, the synthesized tin dioxide-based composite iron(III) oxide has a three-dimensional nanostructure. When used as a tin-based material in the negative electrode coating, it has a larger lithium storage space.
[0131] In some embodiments, the molar ratio of the tin salt to the ferrocyanide salt is (6 to 8):(2 to 4). As an example, the molar ratio of the tin salt to the ferrocyanide salt can be 6:2, 7:3, 8:4. Of course, it can also be a certain ratio within the above range, and no specific limitation is made here.
[0132] In some embodiments, the concentration of the tin salt solution is 2 mol / L to 4 mol / L. As an example, the concentration of the tin salt can be 2 mol / L, 3 mol / L, 4 mol / L. Of course, it can also be a certain point value within the above range, and no specific limitation is made here. Among them, the tin salt solution can be an aqueous solution of the tin salt, preferably an aqueous solution of tin sulfate.
[0133] In some embodiments, the concentration of the ferrocyanide salt solution is 2 mol / L to 4 mol / L. As an example, the concentration of the ferrocyanide salt can be 2 mol / L, 3 mol / L, 4 mol / L. Of course, it can also be a certain point value within the above range, and no specific limitation is made here. Among them, the ferrocyanide salt solution can be an aqueous solution of the ferrocyanide salt.
[0134] In some embodiments, the drying temperature is 500 °C to 700 °C, and the time is 5 h to 7 h. As an example, the drying temperature can be 500 °C, 600 °C, 700 °C. Of course, it can also be a certain point value within the above range, and no specific limitation is made here. As an example, the drying time can be 5 h, 6 h, 7 h. Of course, it can also be a certain point value within the above range, and no specific limitation is made here.
[0135] In some embodiments, the preparation method of the modified lithium titanate includes:
[0136] Mix the modifier, the auxiliary agent and the lithium titanate and then ball-mill them, and then heat them in an inert atmosphere to obtain the modified lithium titanate.
[0137] In some embodiments, the molar ratio of the modifier, the additive, and lithium titanate is (0.8 - 1.2):(0.8 - 1.2):(8 - 12). As an example, the molar ratio of the modifier, the additive, and lithium titanate can be 0.8:0.8:8, 0.8:0.9:10, 1:1:12, 1.2:1.2:12. Of course, it can also be a certain point value within the above range, and specific limitations are not made here. Since the lithium titanate material is a zero-variant material, it is extremely stable during charge and discharge, does not form an SEI film, and does not consume too much active lithium. Its lithium potential is relatively high at 1.5V. Even in the later stage of charging, at low temperature, or during high-rate charging, it will not reach the potential at which lithium ions are reduced to metallic lithium, avoiding the formation of lithium dendrites during overcharging of the battery and having better safety. Coating a layer of lithium titanate on the upper layer of the tin-based composite layer can form a good protective layer, avoiding side reactions between the expanded tin-based negative electrode and the electrolyte, and improving the first efficiency, capacity, cycle stability, and safety of the battery. However, lithium titanate has the disadvantage of poor conductivity. In the present invention, lithium titanate is modified (which can improve the conductivity of lithium titanate. The modifier is equivalent to an SEI film and does not change the advantages inherent in lithium titanate itself), increasing the diffusion and migration rate of lithium ions in the lithium titanate layer (the third negative electrode coating), and thus improving the fast charging ability of the battery.
[0138] In some embodiments, the rotation speed of ball milling is 200 r / min to 400 r / min, and the time is 0.5 h to 2 h. As an example, the rotation speed of ball milling can be 200 r / min, 300 r / min, 400 r / min. Of course, it can also be a certain point value within the above range, and specific limitations are not made here. As an example, the time of ball milling can be 0.5 h, 1 h, 1.5 h, 2 h. Of course, it can also be a certain point value within the above range, and specific limitations are not made here. Limiting the rotation speed and time of ball milling within the above range can achieve a uniform and moderately thick modified coating while maintaining the integrity of lithium titanate particles. If the rotation speed and time are too long, the lithium titanate particles may be overly broken during ball milling, thus affecting the uniformity of the coating. The uniform modified coating can, on the one hand, reduce the film resistance of the electrode sheet and improve the conductivity of the electrode sheet. On the other hand, the modified electrode is beneficial for Li + to be desolvated from the solvation sheath, reducing the interaction between Li + and solvent molecules, thereby accelerating the desolvation kinetics, and thus increasing the diffusion and migration rate of Li + in the lithium titanate layer and improving the fast charging ability of the battery cell.
[0139] In some embodiments, the heating temperature is 700°C to 900°C and the time is 4h to 6h. As an example, the heating temperature can be 700°C, 800°C, 900°C. Of course, it can also be a certain point value within the above range, and no specific limitation is made here. As an example, the heating time can be 4h, 5h, 6h. Of course, it can also be a certain point value within the above range, and no specific limitation is made here.
[0140] Thus, based on the above solution, a carbon-based material is provided in the first negative electrode coating, a tin-based material is provided in the second negative electrode coating, and a modified lithium titanate is provided in the third negative electrode coating. Therefore, by utilizing the characteristic that the carbon-based material has a low expansion rate, the occurrence of the peeling phenomenon between the active material and the current collector during the preparation process of the negative electrode sheet or during the charge and discharge process of the battery due to volume change is reduced; moreover, there is a better adhesion force between the carbon-based material and the current collector. Thus, the service life and safety of the battery can be improved. By controlling the thickness of the first negative electrode coating, on the one hand, it can effectively prevent the contact between the tin-based material and the current collector, improve the adhesion of the membrane, and avoid the membrane peeling phenomenon caused by the expansion of the tin-based material during long-term cycling, thereby improving the cycle stability and safety of the battery. On the other hand, it can enable the capacity of the negative electrode sheet to be effectively exerted to the greatest extent. The tin-based material has a high lithium intercalation capacity, while the graphite and hard carbon are relatively low. A suitable thickness of the graphite and hard carbon composite layer can solve the problem of poor adhesion between the tin-based negative electrode and the current collector, inhibit the large volume expansion of the tin-based negative electrode during the cycling process, and the phenomenon of the modified active substance peeling off the film. On the other hand, it will not cause excessive capacity loss of the overall negative electrode material, and enables the negative electrode to have a larger capacity as much as possible.
[0141] Furthermore, arranging the tin-based material in the second negative electrode coating can prevent the tin-based material from directly contacting the current collector and the electrolyte. First, this setting method can avoid the occurrence of the peeling situation between the tin-based material and the current collector due to the high volume change rate of the tin-based material; second, it can avoid side reactions when the tin-based material contacts the electrolyte, thereby reducing the consumption of active lithium and the capacity attenuation of the battery, and improving the cycle capacity retention rate and long-term stability of the battery.
[0142] Further, the third negative electrode coating contains modified lithium titanate. The modifier is coated on at least part of the surface of lithium titanate to modify the lithium titanate. Since the lithium titanate material is a zero-variation material, it is extremely stable during charge and discharge, does not form an SEI film, and does not consume too much active lithium. Its lithium potential is relatively high at 1.5V. Even in the later stage of charging, at low temperature, or during high-rate charging, it will not reach the potential at which lithium ions are reduced to metallic lithium, avoiding the formation of lithium dendrites during overcharging of the battery and having better safety. Coating a layer of lithium titanate on the upper layer of the tin-based composite layer can form a good protective layer, preventing the swollen tin-based negative electrode from contacting the electrolyte and causing side reactions, and improving the first efficiency, capacity, cycle stability, and safety of the battery. However, lithium titanate has the disadvantage of poor conductivity. In the present invention, the lithium titanate is modified. The modifier coated on the surface of lithium titanate can form an SEI film. At the same time, lithium ions are more likely to undergo a desolvation process at the electrode-electrolyte interface, hindering the contact between solvent molecules and the electrode, suppressing solvent decomposition, and thus forming a thinner SEI and reducing the ion transport resistance within the SEI. Therefore, the diffusion and migration speed of lithium ions in the lithium titanate layer (the third negative electrode coating) can be increased, thereby improving the fast charging ability of the battery.
[0143] Based on the same inventive concept, an embodiment of the present application provides a battery, including a negative electrode sheet, which includes the aforementioned negative electrode sheet or a negative electrode sheet prepared by the aforementioned preparation method.
[0144] Since the battery includes the negative electrode sheet provided by the embodiment of the present application, it has relatively excellent structural stability and electrical properties.
[0145] In some embodiments, the battery can be a lithium-ion battery. The stacking type of the battery is, for example, a wound type or a laminated type battery, and the structural type is, for example, a square shell (aluminum shell, steel shell, etc.) battery, a soft-pack battery, or a cylindrical battery, etc. Specifically, it is not limited. The battery has relatively excellent high-temperature performance and electrical properties.
[0146] In some embodiments, the above battery further includes a positive electrode sheet, an electrolyte, and a separator. That is, the battery includes a positive electrode sheet, a silicon-doped negative electrode sheet, an electrolyte, and a separator.
[0147] In this embodiment, for the positive electrode sheet, materials such as the positive electrode current collector, conductive agent, and binder in the positive electrode active material layer, and the structure are not limited. The structure and composition of the positive electrode sheet that can be used in secondary batteries well-known to those skilled in the art can be selected.
[0148] In this embodiment, the specific material or type of the separator is not limited. The separator that can be used in secondary batteries well-known to those skilled in the art can be selected.
[0149] It should also be noted that for the battery of the present application, the specific materials or types of the electrolyte are not limited, and components and types known to those skilled in the art and applicable to secondary batteries can be selected, as long as the object of the present application can be achieved.
[0150] Since the battery provided by the embodiment of the present invention adopts all the technical solutions of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, which will not be elaborated here one by one.
[0151] The following describes the implementation manners of the present application. The implementation manners described below are exemplary and are only used to explain the present application, and should not be construed as a limitation to the present application. For those technical or conditions not specified in the implementation manners, they shall be carried out according to the technologies or conditions described in the literature in the field or according to the product specifications. For the reagents, materials or instruments not specified for the manufacturer, they are all conventional products that can be obtained through commercial purchase.
[0152] Example 1
[0153] S1: Add the first negative electrode slurry material to deionized water as a solvent according to a proportion and stir to obtain a slurry. Coat the slurry on the surface of a 6-μm-thick copper foil and dry it to complete the coating of the first negative electrode coating;
[0154] In the first negative electrode slurry, the mass ratio of the secondary particle graphitized product of graphite coke as the raw material, hard carbon, conductive carbon, carboxymethyl cellulose, and styrene-butadiene rubber is 86.4:9.6:1:2:1;
[0155] The thickness of the first negative electrode coating is 5 μm;
[0156] S2: Add the second negative electrode slurry material to deionized water as a solvent according to a proportion and stir to obtain a slurry. Coat the slurry on the surface of the first negative electrode coating and dry it to complete the coating of the second negative electrode coating;
[0157] In the second negative electrode slurry, the mass ratio of the tin dioxide-based composite iron oxide, conductive carbon, carboxymethyl cellulose, and polyacrylic acid is 95.6:1:2:1.4;
[0158] Among them, the preparation of the tin dioxide-based composite iron oxide includes:
[0159] Mix an aqueous solution of tin sulfate at 3 mol / L and an aqueous solution of ferricyanide at 3 mol / L according to a molar ratio of 7:3, form a tin-based cyanogel precursor through a sol-gel process, dry it at 600 °C for 6 h under vacuum conditions, wash and dry the product to obtain the tin dioxide-based composite iron oxide;
[0160] The thickness of the second negative electrode coating is 100 μm;
[0161] S3: Add the third negative electrode paste material into deionized water in proportion and stir to obtain a paste. Coat the paste on the surface of the second negative electrode coating and dry to complete the coating of the third negative electrode coating.
[0162] In the third negative electrode paste, the mass ratio of modified lithium titanate, conductive carbon, carboxymethyl cellulose, and styrene-butadiene rubber is 95:2:2:1.
[0163] Among them, the preparation of modified lithium titanate includes:
[0164] Mix lithium dihydrogen phosphate, lithium carbonate, and lithium titanate according to a molar ratio of 6:4:1, then ball mill (ball mill rotation speed 300 r / min, time 1 h). After the ball milling is completed, heat at 800 °C for 5 h in an argon atmosphere to complete the modification of lithium titanate.
[0165] The thickness of the third negative electrode coating is 5 μm.
[0166] S4: Roll press the coated electrode, and the compaction density is 1.5 g / cm 3 .
[0167] Example 2
[0168] The difference between Example 2 and Example 1 is only that the thickness of the first negative electrode coating in Example 2 is 50 μm, the thickness of the second negative electrode coating is 40 μm, and the thickness of the third negative electrode coating is 20 μm.
[0169] Example 3
[0170] The difference between Example 3 and Example 1 is only that the thickness of the first negative electrode coating in Example 3 is 20 μm, the thickness of the second negative electrode coating is 80 μm, and the thickness of the third negative electrode coating is 10 μm.
[0171] Example 4
[0172] The difference between Example 4 and Example 1 is only that in the first negative electrode paste of Example 4, the mass ratio of secondary particle graphitization of graphite coke as the raw material, hard carbon, conductive carbon, carboxymethyl cellulose, and styrene-butadiene rubber is 85:11:1:2:1.
[0173] Example 5
[0174] The difference between Example 5 and Example 1 is only that in the second negative electrode paste of Example 5, the mass ratio of tin dioxide-based composite iron oxide, conductive carbon, carboxymethyl cellulose, and polyacrylic acid is 92.6:4:2:1.4.
[0175] Example 6
[0176] The difference between Example 6 and Example 1 is only that in Example 6, tin dioxide-based composite iron oxide is replaced with tin.
[0177] Example 7
[0178] The difference between Example 7 and Example 1 is only that in Example 7, the tin dioxide-based composite iron oxide is replaced with tin dioxide.
[0179] Example 8
[0180] The difference between Example 8 and Example 1 is only that in Example 8, the mass ratio of modified lithium titanate, conductive carbon, carboxymethyl cellulose, and styrene-butadiene rubber in the third negative electrode paste is 92:5:2:1.
[0181] Example 9
[0182] The difference between Example 9 and Example 1 is that when preparing modified lithium titanate in Example 9, lithium dihydrogen phosphate, lithium carbonate, and lithium titanate are in a molar ratio of 6:4:3.
[0183] Example 10
[0184] The difference between Example 10 and Example 1 is that the preparation of modified lithium titanate in Example 10 includes:
[0185] Lithium sulfate, lithium carbonate, and lithium titanate are mixed in a molar ratio of 6:4:1, then ball-milled (ball-milling speed 300 r / min, time 1 h). After the ball-milling is completed, it is heated at 800 °C for 5 h in an argon atmosphere to complete the modification of lithium titanate.
[0186] Example 11
[0187] The difference between Example 11 and Example 1 is only that when preparing modified lithium titanate in Example 11, the ball-milling speed is 400 r / min and the time is 1.5 h.
[0188] Comparative Example 1
[0189] The difference between Comparative Example 1 and Example 3 is only that Comparative Example 1 does not have the first negative electrode coating.
[0190] Comparative Example 2
[0191] The difference between Comparative Example 2 and Example 3 is only that Comparative Example 2 does not have the third negative electrode coating.
[0192] Comparative Example 3
[0193] The difference between Comparative Example 3 and Example 3 is only that Comparative Example 3 does not have the first negative electrode coating and the third negative electrode coating.
[0194] Performance Test
[0195] 1. Battery Preparation
[0196] Preparation of the positive electrode sheet: Lithium iron phosphate as the positive electrode material, conductive carbon black (SP) as the conductive agent, and polyvinylidene fluoride (PVDF5130) as the binder were added to a stirring tank in a mass ratio of 97:1:2 and stirred and mixed for 30 min. Then, N-methylpyrrolidone (NMP) as the solvent was added, and stirring continued for 30 min. Subsequently, stirring was carried out for 3 h under a vacuum environment to obtain a uniformly mixed positive electrode paste. The obtained positive electrode paste was coated on the current collector, and after high-temperature drying, rolling, and die-cutting, the positive electrode sheet was obtained.
[0197] Separator: A polyethylene (PE) separator with a thickness of 12 μm was selected as the separator.
[0198] Preparation of the electrolyte: In a glove box filled with inert gas, ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1:1, and then LiPF6 was added and mixed evenly. The concentration of the lithium salt was 1 mol / L to obtain the electrolyte.
[0199] Assembly of the battery: The positive electrode sheet, separator, and negative electrode sheet were wound according to the principle of the separator wrapping the negative electrode and the negative electrode wrapping the positive electrode. After winding, hot pressing was carried out, and it was placed in an aluminum shell. Through the processes of liquid injection, formation, and grading, the lithium-ion battery was obtained.
[0200] 2. Electrochemical performance testing of the battery
[0201] (1) Initial efficiency test: The assembled lithium-ion batteries of each example and comparative example were charged and discharged respectively. Charging was carried out at a constant current of 0.33C to 3.65V, then at a constant current of 3.65V to 0.05C. The charging capacity was denoted as Cn. Discharging was carried out at a constant current of 0.33C to the lower limit voltage of 2.5V, and the capacity was denoted as Cn+1. The initial efficiency = (Cn / Cn+1) * 100%.
[0202] (2) Capacity retention rate test after 500 cycles: The lithium-ion batteries prepared in each example and comparative example were left standing at 25°C for 30 min, discharged at a constant current of 1C, left standing for 30 min, then charged at a constant current of 1C to 3.65V, charged at a constant current of 3.65V to 0.05C, left standing for 30 min, discharged at a constant current of 1C to 2.5V, left standing for 30 min, charged at a constant current of 1C to 3.65V, charged at a constant current of 3.65V to 0.05C, and left standing for 30 min. A cycle test was carried out in this mode for 500 cycles, and the ratio of the discharge capacity in the 500th cycle to the discharge capacity in the first cycle was recorded as the capacity retention rate (Note: The higher the capacity retention rate, the longer the service life of the electrode sheet).
[0203] (3) Test of the pole piece rebound rate after 500 cycles: Each of the examples and comparative examples of the battery after 500 cycles of charge was fully charged and disassembled, and the thickness of the negative pole piece was measured. The pole piece rebound rate after 500 cycles = (the thickness of the negative pole after 500 cycles - the thickness of the negative pole after rolling) / (the thickness of the negative pole after rolling - the thickness of the negative pole current collector) * 100%.
[0204] The specific test results are shown in Table 1 below.
[0205] Table 1
[0206]
[0207]
[0208] Comparing the test data of Examples 1 to 3, it can be seen that the thicker the thickness of the modified lithium titanate layer, the higher the initial efficiency of the battery, the higher the capacity retention rate, and the smaller the rebound of the negative pole piece. It shows that the modified lithium titanate can prevent the side reactions caused by the contact between the tin-based negative pole layer and the electrolyte, inhibit the rebound of the tin-based material, and thus effectively improve the initial efficiency, capacity and cycle life of the battery.
[0209] Comparing the test data of Example 4 and Comparative Example 1, it can be seen that increasing the proportion of hard carbon in the bottom layer graphite and hard carbon composite layer reduces the overall rebound of the negative pole piece, but since the capacity of hard carbon is smaller than that of graphite, the capacity retention rate of the whole battery cell decreases.
[0210] Comparing the test data of Example 5 and Comparative Example 1, it can be seen that reducing the proportion of the intermediate layer tin dioxide-based composite iron oxide does not significantly improve the expansion of the negative pole piece. Because the volume expansion of the tin-based material is relatively large, simply reducing the content will not significantly reduce the expansion of the negative pole piece, and the cooperation of the bottom layer and the top layer composite layer is required.
[0211] Comparing the test data of Example 6, Example 7 and Comparative Example 1, it can be seen that replacing the intermediate layer tin dioxide-based composite iron oxide with tin and tin dioxide, since the expansion of tin and tin dioxide is larger than that of tin dioxide-based composite iron oxide, the expansion of the negative pole piece of the battery cell after 500 cycles increases significantly, and the initial efficiency and capacity retention rate of the battery cell decrease accordingly. The expansion degree of SnO2 is usually more significant than that of Sn, because SnO2 not only involves volume changes during charge and discharge, but also is accompanied by a phase change process, so the performance of the battery cell is worse after the intermediate layer is replaced with SnO2.
[0212] Comparing the test data of Example 8 and Comparative Example 1, it can be seen that changing the formula of the top layer and reducing the mass proportion of the modified lithium titanate slightly reduces the overall performance of the battery cell, but within this formula range, the difference is not significant.
[0213] By comparing the test data of Example 9 and Comparative Example 1, it can be seen that by changing the preparation ratio of the top modified lithium titanate, keeping the proportion of lithium dihydrogen phosphate and lithium carbonate unchanged, and increasing the content of lithium titanate, the overall performance of the battery cell is reduced. Due to the increase in the content of lithium titanate in the coated body, the uniformity of the coating may be reduced. + The migration of the battery is reduced, thereby reducing the initial efficiency of the battery cell and reducing the capacity retention rate.
[0214] Comparing the test data of Example 10 and Comparative Example 1, it can be seen that when the top modifier lithium dihydrogen phosphate is replaced by lithium sulfate, the overall performance of the battery cell deteriorates. This is because the Li + The activation energy of desolventization is higher than that of Li2SO4 enriched in SEI. + The activation energy of desolventization is low, and the enrichment of lithium sulfate in SEI is more conducive to Li + Desolvation from the solvent sheath, Li + The transmission rate is faster, and the first efficiency and capacity retention rate of the battery cell are higher.
[0215] By comparing the test data of Example 11 with that of Comparative Example 1, it can be seen that increasing the speed and time of preparing the top layer of modified lithium titanate slightly reduces the overall performance of the battery cell. Too long a speed and time may cause excessive crushing of lithium titanate particles during the ball milling process, thereby affecting the uniformity of the coating layer, reducing the conductivity of the pole piece, and Li + The diffusion migration speed in the lithium titanate layer slows down, and the initial efficiency and capacity retention rate of the battery cell decrease.
[0216] From the test data of Comparative Example 3 and Comparative Example 1, it can be seen that with the presence of graphite and hard carbon composite layer, the graphite and hard carbon composite layer undertake the combination of the current collector and the tin-based negative electrode layer, improve the adhesion between the tin-based negative electrode layer and the current collector, and the smaller the rebound of the electrode piece, it means that the presence of graphite and hard carbon layer can avoid direct contact between the tin-based negative electrode material and the current collector, thereby suppressing the rebound of the tin-based negative electrode material to a certain extent.
[0217] By comparing the test data of Example 3 and Comparative Example 2, it can be seen that with the provision of a modified lithium titanate protective layer, the tin-based negative electrode layer is not in direct contact with the electrolyte, thereby reducing the side reaction between the tin-based negative electrode layer and the electrolyte, and reducing the pulverization of the tin-based material during the cycle and the continuous consumption of active lithium, thereby improving the initial efficiency and cycle life of the battery cell, inhibiting the expansion of the tin-based negative electrode material layer, and reducing the rebound of the electrode piece.
[0218] Comparing the test data of Comparative Example 3 and Comparative Example 3, it can be seen that with the setting of the bottom graphite layer, hard carbon composite layer, and top modified lithium titanate layer, the initial efficiency, capacity retention rate, and electrode sheet rebound of the battery cell have obvious advantages. For the electrode sheet of the battery cell without the top modified lithium titanate coating, the rebound of the tin-based negative electrode sheet is relatively large. The tin-based layer is in direct contact with the electrolyte. As the volume of the tin-based layer expands, the SEI film is continuously formed, consuming a large amount of active lithium, resulting in a relatively rapid decline in the capacity retention rate of the battery cell. Similarly, without the setting of the bottom graphite layer and hard carbon composite layer, the tin-based layer is directly coated on the current collector. As the volume of the tin-based layer expands, the contact between the tin-based layer and the current collector is poor, and the risk of the electrode sheet peeling off is very high, which will further accelerate the attenuation of the battery cell capacity.
[0219] In summary, a composite negative electrode sheet provided by the present invention is provided with a graphite layer, a hard carbon composite layer, a tin-based negative electrode layer, and a modified lithium titanate layer. By setting the graphite and hard carbon composite layer at the bottom layer, the adhesion between the active material and the current collector is effectively improved, and the rebound caused by volume change during the manufacturing process of the tin-based negative electrode sheet and during the charge and discharge process of the battery is reduced, resulting in the phenomenon of peeling between the active material and the current collector, thereby greatly improving the service life and safety performance of the lithium-ion battery. By setting a modified lithium titanate layer on the upper layer of the tin-based negative electrode material layer, the modifier in the modified lithium titanate layer is rich in inorganic SEI, which accelerates the interfacial transmission of Li + . Because the desolvation process is more likely to occur at the electrode-electrolyte interface, the contact between the solvent molecules and the electrode is hindered, the solvent decomposition is inhibited, resulting in the formation of a thinner SEI, and reducing the ionic transport resistance within the SEI. It is possible to avoid side reactions caused by the contact between the tin-based composite material layer and the electrolyte, reduce the consumption of active lithium in the battery and the capacity attenuation, and improve the cycle capacity retention rate and long-term stability of the battery.
[0220] The parts not described in detail in the present invention are well-known technologies to those skilled in the art.
[0221] The basic principles of the present invention have been described above in conjunction with specific embodiments. However, it should be noted that the advantages, advantages, effects, etc. mentioned in the present invention are only examples and not limitations. It cannot be considered that these advantages, advantages, effects, etc. are essential for each embodiment of the present invention. In addition, the above-disclosed specific details are only for the purposes of illustration and easy understanding, rather than limitations. The above details do not limit the present invention to necessarily adopt the above specific details to implement.
[0222] It should be noted that the term "and / or" or " / " used in this text is merely a description of the association relationship between associated objects, indicating that three relationships can exist. For example, A and / or B can represent three situations: A exists alone, A and B exist simultaneously, and B exists alone. The singular forms of "a", "the", and "said" used in the embodiments of the present invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.
[0223] In the specific embodiments and the claims, a list of items connected by the terms "at least one of", "at least one in", "at least one kind in", or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0224] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements for some of the technical features; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises: current collector; A first negative electrode coating is disposed on at least one side of the current collector along the thickness direction, and the first negative electrode coating comprises a carbon-based material; A second negative electrode coating is disposed on a surface of the first negative electrode coating away from the current collector, wherein the second negative electrode coating comprises a tin-based material; and The third negative electrode coating is arranged on a surface of the second negative electrode coating away from the first negative electrode coating, and the third negative electrode coating comprises modified lithium titanate.
2. The negative electrode sheet according to claim 1, characterized in that: The first negative electrode coating satisfies at least one of the following characteristics (1) to (3): (1) The carbon-based material includes hard carbon and graphite; The mass ratio of the hard carbon to the graphite is (5-15):(85-95); Preferably, the graphite includes at least one of graphitized needle coke, graphitized asphalt tar, and graphitized petroleum coke; preferably, the graphite is selected from graphitized petroleum coke; (2) The first negative electrode coating further includes a first conductive agent and a first binder; The mass ratio of the carbon-based material, the first conductive agent and the first binder is (90-110): (0.3-1): (2-3); Preferably, the first conductive agent includes at least one of conductive carbon black, conductive carbon fiber, graphene or conductive carbon nanotubes; Preferably, the first binder includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium alginate or polyacrylic acid; (3) The thickness of the first negative electrode coating layer is 5 μm to 50 μm.
3. The negative electrode sheet according to claim 1, characterized in that: The second negative electrode coating satisfies at least one of the following characteristics (1) to (3): (1) The tin-based material includes at least one of tin element, tin oxide compound, and tin alloy; Preferably, the tin-based material comprises tin dioxide-based composite iron oxide; (2) The second negative electrode coating further includes a second conductive agent and a second binder; The mass ratio of the tin-based material, the second conductive agent and the second binder is (90-96): (0.5-1): (2-3.5); Preferably, the second conductive agent includes at least one of conductive carbon black, conductive carbon fiber, graphene or conductive carbon nanotubes; Preferably, the second binder includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium alginate or polyacrylic acid; (3) The thickness of the second negative electrode coating layer is 40 μm to 100 μm.
4. The negative electrode sheet according to claim 1, characterized in that: The third negative electrode coating satisfies at least one of the following characteristics (1) to (3): (1) The modified lithium titanate comprises a modifier and lithium titanate, and the modifier is coated on at least a portion of the surface of the lithium titanate; The mass ratio of lithium titanate to the modifier in the modified lithium titanate is (85-95): (5-15); Preferably, the modifier includes lithium phosphate, lithium dihydrogen phosphate, lithium sulfate, and lithium sulfite; (2) The third negative electrode coating further includes a third conductive agent and a third binder; The mass ratio of the modified lithium titanate, the third conductive agent and the third binder is (90-95): (1-2): (1.5-3); Preferably, the third conductive agent includes at least one of conductive carbon black, conductive carbon fiber, graphene or conductive carbon nanotubes; Preferably, the third binder includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, sodium alginate or polyacrylic acid; (3) The thickness of the third negative electrode coating is 5 μm to 20 μm.
5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The current collector includes at least one of copper foil, nickel foam, nickel mesh or composite copper foil.
6. A method for preparing a negative electrode sheet, characterized in that: The following steps are involved: Coating a first negative electrode slurry on at least one side of the current collector to obtain a first negative electrode coating; Coating a second negative electrode slurry on the surface of the first negative electrode coating to obtain a second negative electrode coating; coating a third negative electrode slurry on the surface of the second negative electrode coating to obtain a third negative electrode coating; Rolling and drying the current collector coated with the first negative electrode coating, the second negative electrode coating, and the third negative electrode coating; Wherein, the first negative electrode coating comprises a carbon-based material; The second negative electrode coating comprises a tin-based material; The third negative electrode coating layer includes modified lithium titanate.
7. The method for preparing a negative electrode sheet according to claim 6, characterized in that: The preparation of the first negative electrode slurry includes: mixing hard carbon, graphite, a first conductive agent and a first binder in a solvent to obtain a first negative electrode slurry; The preparation of the second negative electrode slurry includes: uniformly mixing the tin-based material, the second conductive agent and the second binder in a solvent to obtain the second negative electrode slurry; The preparation of the third negative electrode slurry includes: uniformly mixing the modified lithium titanate, the third conductive agent and the third binder in a solvent to obtain the third negative electrode slurry; The compaction density of the roller is 1.45-1.65 g / cm 3 ; Preferably, the solvent comprises at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, N-methylpyrrolidone, water or ethylene carbonate; Preferably, the first negative electrode slurry is coated on the surface of the current collector, and after drying, a first negative electrode coating is formed on the surface of the current collector; the second negative electrode slurry is coated on the first negative electrode coating, and after drying, a second negative electrode coating is formed on the surface of the first negative electrode coating; the third negative electrode slurry is coated on the second negative electrode coating, and dried; the current collector coated with the first negative electrode coating, the second negative electrode coating, and the third negative electrode coating is roll-pressed and dried to obtain a negative electrode sheet.
8. The method for preparing a negative electrode sheet according to claim 6, characterized in that: The tin-based material includes a tin dioxide-based composite ferric oxide, and the preparation method of the tin dioxide-based composite ferric oxide includes: The tin salt solution and the ferrocyanide solution are mixed to form a tin-based cyanide gel precursor through a sol-gel process, and after drying and washing, a tin dioxide-based composite ferric oxide is obtained; the molar ratio of the tin salt to the ferrocyanide is (6-8): (2-4); Preferably, the concentration of the tin salt solution is 2 to 4 mol / L; Preferably, the drying temperature is 500° C. to 700° C., and the drying time is 5 h to 7 h.
9. The method for preparing a negative electrode sheet according to claim 6, characterized in that: The preparation method of the modified lithium titanate comprises: The modifier, the auxiliary agent and lithium titanate are mixed and ball-milled, and then heated under an inert atmosphere to obtain modified lithium titanate; The molar ratio of the modifier, the auxiliary agent and lithium titanate is (0.8-1.2): (0.8-1.2): (8-12); Preferably, the ball milling speed is 200-400 r / min, and the time is 0.5h-2h; Preferably, the heating temperature is 700° C. to 900° C., and the heating time is 4 h to 6 h.
10. A battery comprising a negative electrode sheet, characterized in that: The negative electrode sheet includes the negative electrode sheet according to any one of claims 1 to 5, or includes the negative electrode sheet prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Cited By
Negative plate, preparation method thereof and battery
CN120809801A